The Cephennium fauna of Turkey and the Middle East (Coleoptera: Staphylinidae: Scydmaeninae) - Assing, Volker; Meybohm, Heinrich (Contributions to Entomology = Beiträge zur Entomologie, 2021)
Only two species of Cephennium Muller & Kunze, 1822 were previously known from Turkey and the Middle East including Lebanon, Israel, Jordan, Iraq, and Iran. An examination of material collected during numerous field trips toTurkey and Jordan in the past four decades revealed that the Cephennium fauna of Turkey is remarkably diverse. In total, 25 named species are recognized, diagnosed, illustrated, and assigned to four species groups. Based on zoogeographic, morphological, and additional evidence, C. bodemeyeri Reitter, 1903, previously a subspecies of C. perispinctum Kolenati, 1846, is elevated to species rank. Twenty-three species are described for the first time: Cephennium fractum spec. nov. (Turkey: Bursa, Balıkesir, Kocaeli, Canakkale), C. infractum spec. nov. (Turkey: Bursa), and C. immutatum spec. nov. (Turkey: Izmir, Muğla, Adıyaman) of the C. perispinctum group; C. ericinum spec. nov. (Turkey: Ordu), C. varispinosum spec. nov. (Turkey: Ordu), C. victrix spec. nov. (Turkey: Sinop), C. spinigerum spec. nov. (Turkey: Bartin), and C. digitale spec. nov. (Turkey: Zonguldak) of the C. ericinum group; C. reductum spec. nov. (Turkey: Konya, Antalya, Mersin, Kastamonu) of the C. jonicum group; C. corruptum spec. nov. (Turkey: Mersin, Adana), C. marasicum spec. nov. (Turkey: Kahramanmaraş), C. dolucanum spec. nov. (Turkey: Kahramanmaraş), C. fimbriatum spec. nov. (Turkey: Adana), C. besucheti spec. nov. (Turkey: Kahramanmaraş), C. affimbriatum spec. nov. (Turkey: Kahramanmaraş), C. kartalicum spec. nov. (Turkey: Gaziantep), Cephennium nemruticum spec. nov. (Turkey: Adıyaman), C. unguicum spec. nov. (Turkey: Aydın), C. deplectens spec. nov. (Turkey: Izmir, Manisa), C. sicaferum spec. nov. (Turkey: Aydın), C. geminum spec. nov. (Turkey: Antalya), C. duplum spec. nov. (Turkey: Muğla), and C. jordanicum spec. nov. (Northwest Jordan) of the C. corruptum group. Several additional species, all of them represented exclusively by females and most likely belonging to the C. corruptum group, remain undescribed. A key to the named species of Turkey and the Middle East is provided. The distributions of the species recorded from Turkey are mapped. In an appendix, C. liguliferum spec. nov. (Southeast Bulgaria), a close relative of C. bodemeyeri and C. perispinctum, is described and illustrated.Taxonomic actsCephennium fractum spec. nov. – urn:lsid:zoobank.org:act:26CE8301-2927-4893-B93E-9F2BEF4F7F07Cephennium infractum spec. nov. – urn:lsid:zoobank.org:act:E222C4A2-D6AC-48FF-AC4C-B274EF405209Cephennium immutatum spec. nov. – urn:lsid:zoobank.org:act:F24C0315-7B6F-427E-B9AB-65AB304F7718Cephennium ericinum spec. nov. – urn:lsid:zoobank.org:act:F56474A9-C330-4019-BD58-B566E66CF58ECephennium varispinosum spec. nov. – urn:lsid:zoobank.org:act:04C4304D-F84A-400B-8710-15407DE9BCCDCephennium victrix spec. nov. – urn:lsid:zoobank.org:act:2BC2443C-70A2-4B5B-874A-FAF0F4DCFB62Cephennium spinigerum spec. nov. – urn:lsid:zoobank.org:act:7321FC90-18ED-4F50-8CFA-58F338EA62BBCephennium digitale spec. nov. – urn:lsid:zoobank.org:act:06ED0DE9-D72E-410C-9A7A-B7330175D3D9Cephennium reductum spec. nov. – urn:lsid:zoobank.org:act:CB292C96-5EC1-4947-AE0F-3D3F3094C77ACephennium corruptum spec. nov. – urn:lsid:zoobank.org:act:BC5C6DE3-2696-4949-B84F-E7336C5DC774Cephennium marasicum spec. nov. – urn:lsid:zoobank.org:act:02420408-99DB-49FA-8A5B-409528E5613ACephennium dolucanum spec. nov. – urn:lsid:zoobank.org:act:F0BFE9A7-0AE9-40D2-BC5E-49DE875B2A65Cephennium fimbriatum spec. nov. – urn:lsid:zoobank.org:act:831C051F-751A-4D9C-A9DA-7E2BCAA4D82ECephennium besucheti spec. nov. – urn:lsid:zoobank.org:act:831C051F-751A-4D9C-A9DA-7E2BCAA4D82ECephennium affimbriatum spec. nov. – urn:lsid:zoobank.org:act:02ED0B80-53CF-4ED8-8648-F45DC12696B5Cephennium kartalicum spec. nov. – urn:lsid:zoobank.org:act:27B66398-BD3C-4C54-9DF8-0918EEEB6C65Cephennium nemruticum spec. nov. – urn:lsid:zoobank.org:act:643B8783-90BC-4DE2-9DA7-45EFCF67778CCephennium unguicum spec. nov. – urn:lsid:zoobank.org:act:92FD91A3-6A6F-4EBB-BBBF-2CA222D6FD14Cephennium deplectens spec. nov. – urn:lsid:zoobank.org:act:E16431E9-E6B9-411F-B164-3FA1B7A4D2E2Cephennium sicaferum spec. nov. – urn:lsid:zoobank.org:act:7F1029CB-AD9C-42A6-BBAC-5BDC653EBFECCephennium geminum spec. nov. – urn:lsid:zoobank.org:act:36759AD0-8CA5-44E3-A0A0-D50329D09B0CCephennium duplum spec. nov. – urn:lsid:zoobank.org:act:B2B65A3E-757E-44EB-9F6F-C46D7523A3EBCephennium jordanicum spec. nov. – urn:lsid:zoobank.org:act:900BF391-A399-4559-A132-F1E8F1CFB3E7Cephennium liguliferum spec. nov. – urn:lsid:zoobank.org:act:BE39D1DA-3677-435F-A8EB-D34BE361F9F5
Keywords: Coleoptera; Staphylinidae; Scydmaeninae; Cephennium; taxonomy; new species; species groups; West Palaearctic; Middle East; Turkey; Jordan; Bulgaria; endemism; distribution maps